Hyperprolactinemia: A Systematic Review of Diagnosis and Management (Delta Medical College Journal, 2018)
Hyperprolactinemia is a common endocrine disorder that can be associated with significant morbidity. It can result from a number of causes, including use of medication, hypothyroidism and pituitary disorders. Depending on the cause and consequences of hyperprolactinemia, selected patients require treatment considering the underlying cause, age sex, and reproductive status. We describe a systematic review of hyperprolactinemia, including microadenomas and macroadenomas, in various clinical settings, with emphasis on newer diagnostic strategies and the role of various therapeutic options, including treatment with selective dopamine agonists. Through this review, we aimed to compare efficacy and adverse effects of medications, surgery and radiotherapy in the treatment of hyperprolactinemia.Delta Med Col J. Jan 2018 6(2): 90-101